Early-onset pneumonia following bag-mask ventilation versus endotracheal intubation during cardiopulmonary resuscitation: A substudy of the CAAM trial - Baekgaard, Josefine S.; Triba, Mohamed N.; Brandeis, Morgane; Steinmetz, Jacob; Cohen, Yves; Gorlicki, Judith; Rasmussen, Lars S.; Deltour, Sandrine; Lapostolle, Frédéric; Adnet, Frédéric (Resuscitation, 2020)
Early-onset pneumonia (EOP) is a common in-hospital complication in survivors of out-of-hospital cardiac arrest. In this substudy of the CAAM trial, we aimed to compare whether bag mask ventilation (BMV) compared to endotracheal intubation (ETI) performed during cardiopulmonary resuscitation increases the risk of developing EOP. Adult patients from the CAAM trial that survived beyond 12 h of hospitalization were included. Information about in-hospital management and outcome of study subjects was systematically collected. Our primary aim was to compare the incidence of EOP in the BMV and ETI group using a series of bivariate analysis adjusting for one variable at a time and a logistic regression controlled for survival beyond 96 h, age, gender, catecholamine administration, no flow time, and initial shockable rhythm. Of 627 patients from the CAAM trial that survived to hospital admission, 409 patients were hospitalized beyond 12 h and thus included (202 randomized to BMV and 20 7 randomized to ETI). Patients in the BMV group had a significantly longer period of unsecured airway during prehospital cardiopulmonary resuscitation (BMV (median): 33 min; ETI (median): 17 min, p < 0.0001). No significant difference in the development of EOP according to airway management was identified on univariate analysis (BMV: 53%, ETI: 53%, Odds Ratio 1.0 [0.7–1.5], p = 1.0). We found no difference in the development of EOP according to airway management in the series of bivariate analyses or in the multivariable regression analysis either. In this substudy of the CAAM trial, development of early-onset pneumonia in out-of-hospital cardiac arrest survivors did not depend on airway management technique during CPR.